Mitigating Digital Era Challenges Through Curriculum Integration: Islamic Education and Pancasila Student Profile in Primary Schools - Mursal Aziz; Dedi Sahputra Napitupulu; Maisah Erawati (International Journal of Educational Qualitative Quantitative Research, 2026)
Amidst escalating digital disruptions and emerging ethical vulnerabilities among primary school learners, establishing robust self-regulatory character anchors has become an international educational imperative. Drawing on Values Cultivation and Digital Citizenship frameworks, this exploratory qualitative case study examines the operationalization of an integrated curriculum merging the Islamic Education Curriculum and the national Pancasila Student Profile to mitigate digital-era moral degradation in a peripheral public primary school setting. Data were accrued through prolonged participant observations, semi-structured interviews with key institutional stakeholders (the principal, educators, students, and parents), and extensive textual documentation, which were systematically processed using rigorous thematic analysis to ensure data trustworthiness. The findings illuminate a tripartite structural mechanism driving integration: spiritual-affective habituation (routine worship), behavioral modeling by educators, and institutional value-embedding within the school culture, structurally reinforced through the Pancasila Student Profile Strengthening Project (P5). This synergistic curriculum effectively fosters critical character tenets, including social discipline, moral accountability, honesty, and empathy, which serve as cognitive anchors that insulate students from virtual-space distractions and behavioral fragmentation. However, systemic bottlenecks persist, including pervasive digital inequities, pedagogical conservatism, and infrastructural deficits. To circumvent these barriers, the institution deploys multi-stakeholder synergetic networks and iterative character tracking. Ultimately, this study conceptualizes a 'Civic-Religious Synergistic Pedagogy' model, concluding that a symbiotic alignment between religious education and civic profiles provides a scalable, sustainable framework for developing nations navigating the critical nexus of rapid technological integration and youth moral stabilization.